Effect of frequency boundary assignment on speech recognition with the Nucleus 24 ACE speech coding strategy. - Fourakis MS; Hawks JW; Holden LK; Skinner MW; Holden TA (Journal of the American Academy of Audiology, 2007)
The choice of frequency boundaries for the analysis channels of cochlear implants has been shown to impact the speech perception performance of adult recipients (Skinner et al, 1995; Fourakis et al, 2004). While technological limitations heretofore have limited the clinical feasibility of investigating novel frequency assignments, the SPEAR3 research processor affords the opportunity to investigate an unlimited number of possibilities. Here, four different assignments are evaluated using a variety of speech stimuli. All participants accommodated to assignment changes, and no one assignment was significantly preferred. The results suggest that better performance can be achieved using a strategy whereby (1) there are at least 7-8 electrodes allocated below 1000 Hz, (2) the majority of remaining electrodes are allocated between 1100-3000 Hz, and (3) the region above 3 kHz is represented by relatively few electrodes (i.e., 1-3). The results suggest that such frequency assignment flexibility should be made clinically available.